Towards Designing for the Postdigital Hybrid Workplace: A Systematic Literature Review - Tahsiri, Mina (Enquiry The ARCC Journal for Architectural Research, 2023)
This paper frames the future workplace as a postdigital hybrid space of practice that foregrounds humanistic values and holistically accommodates various requirements of individuals and collectives who make up the socio-cultural context of the workplace, wherever work may occur. However, to move towards designing for the postdigital hybrid workplace, it is necessary to first have an overview of the requirements foreseen for the future of workplace that are pertinent to notions of the postdigital and hybridity within the scholarly domain. On this basis, the paper presents a Systematic Literature Review (SLR) of workplace design and management literature (2010-2022) informed by the PRISMA 2020 guidelines. Studies were sourced through Scopus and Google Scholar, and screened for comprehension, relevancy, and certainty. Studies were appraised for quality before inclusion in the SLR, using a framework that combines a Weight of Evidence (WoE) framework (Gough 2007) with a set of appraisal criteria that can be used in qualitative research (Hannes 2011). Through a thematic analysis of the final 37 studies, the following seven requirements were identified: 1) embodied, intuitive and multimodal experiences, 2) a balance between privacy and interaction, 3) environmental comfort, 4) disconnection, 5) a culture that empowers the individual, 6) social territories and collective synergies, and 7) heterogeneity. The paper discusses that collectively the requirements identified signify the importance of the socio-spatial context in which work occurs. Therefore, as the ecosystem of work continues to change and adapt to hybridity, changes in meanings, perceptions and behaviours related to these requirements should be further investigated in order to better support design and management strategies. In addition, the paper acknowledges the inevitable juxtapositions of opposing expectations and requirements in a flexible workplace, and brings light to the behavioural, temporal and connectivity dimensions under which rivalling issues should be considered for a postdigital hybrid workplace.